Analisis Potensi Pencemaran Air Tanah Bebas di Lereng Kaki Koluvial dan Dataran Aluvial Daerah Aliran Sungai Pesing Menggunakan Integrasi Metode GOD dan SIG Berbasis Web: Analysis of Potential Groundwater Pollution in Unconfined Aquifer in Colluvial Footslopes and Alluvial Plains of the Pesing Watershed Using Integration of GOD and GIS Web Based Methods - SEJATI, SADEWA PURBA; SAPUTRA, ADITYA (Jurnal Teknologi Lingkungan, 2022)
ABSTRACT Agricultural, livestock, and domestic activities in the alluvial plains and the colluvial footslopes of the Pesing watershed have the potential to reduce groundwater quality in an unconfined aquifer. Environmental characteristics need to be identified spatially to determine the potential for groundwater contamination. The latest mapping technology also needs to be identified to determine its ability to disseminate information on potential groundwater pollution. The research was conducted to determine the potential for groundwater pollution and to identify the capability of a web-based GIS as a medium for disseminating geospatial information. Potential groundwater contamination was identified using the GOD method. The variables used include the type of aquifer, aquifer lithology, and groundwater depth. Variables of aquifer type and aquifer lithology are known through secondary data, namely drilling data, geological data, and literature studies. Variable groundwater depth is known through field surveys. Sampling method used is systematic random sampling. Each variable is classified and visualized in the form of a thematic map. Three variables were analyzed by the overlay method. Based on the results of the analysis, it is known that in the rainy season, the research area is classified into three classes of potential for groundwater pollution, namely extreme potential with a percentage of 27% area, high potential with a rate of 71%, and medium potential with a percentage of 2%. The potential for groundwater contamination during the dry season is classified into two classes: high potential with an area of 43% and medium potential with a percentage of 57%. Temporal dynamics of the potential for groundwater pollution are caused by a variable sensitive to seasonal changes, namely the depth of groundwater. The land uses that have the most influence on the potential for groundwater contamination are rice fields and livestock manure disposal. Web-based GIS can be used as a medium for disseminating information on potential groundwater pollution. The program can be appropriately operated on a variety of electronic devices. Web-based GIS is equipped with a variety of features that can be used interactively for fundamental to applied analysis. Keywords: groundwater, unconfined aquifer, GOD, GIS, web   ABSTRAK Aktivitas pertanian, peternakan, dan domestik di dataran aluvial dan dataran kaki koluvial DAS Pesing berpotensi menurunkan kualitas air tanah bebas. Karakteristik lingkungan perlu diidentifikasi secara spasial untuk mengetahui potensi pencemaran air tanah. Teknologi pemetaan terkini juga perlu diidentifikasi untuk mengetahui kemampuannya dalam mendiseminasi informasi potensi pencemaran air tanah. Penelitian dilakukan untuk mengetahui potensi pencemaran air tanah dan mengidentifikasi kemampuan sistem informasi geografis berbasis (SIG) web sebagai media diseminasi informasi geospasial. Potensi pencemaran air tanah diidentifikasi menggunakan metode GOD (groundwater occurrence, overall lithology of aquifer, depth to water table). Variabel yang digunakan meliputi jenis akuifer, litologi akuifer, dan kedalaman air tanah. Variabel jenis akuifer dan litologi akuifer diketahui melalui data sekunder, yaitu data pengeboran, data geologi, dan studi literatur. Variabel kedalaman air tanah diketahui melalui survei lapangan. Metode sampling yang digunakan adalah acak bersistem. Setiap variabel diklasifikasi dan divisualkan dalam bentuk peta tematik. Ketiga variabel dianalisis dengan metode overlay. Berdasarkan hasil analisis diketahui bahwa pada musim hujan daerah penelitian terklasifikasi menjadi tiga kelas potensi pencemaran air tanah bebas, yaitu potensi ekstrim dengan persentase luas 27%, potensi tinggi dengan persentase 71%, dan potensi sedang dengan persentase 2%. Potensi pencemaran air tanah pada musim kemarau terklasifikasi menjadi dua kelas, yaitu potensi tinggi dengan persentase luas 43% dan potensi sedang dengan persentase 57%. Dinamika temporal potensi pencemaran air tanah bebas disebabkan karena terdapat variabel yang sensitif terhadap perubahan musim, yaitu kedalaman air tanah. Penggunaan lahan yang paling berpengaruh terhadap potensi pencemaran air tanah adalah sawah dan lokasi pembuangan kotoran ternak. SIG berbasis web mampu digunakan sebagai media diseminasi informasi potensi pencemaran air tanah bebas. Program dapat dioperasikan dengan baik pada beragam perangkat elektronik. Program dilengkapi dengan beragam fitur yang dapat digunakan secara interaktif untuk analisis dasar hingga terapan. Kata kunci: air tanah, akuifer bebas, GOD, SIG, web